FULMINANT CLOSTRIDIUM SEPTICUM ENDOGENOUS ENDOPHTHALMITIS PRESENTING WITH INTRAOCULAR GAS IN A PATIENT WITH METASTATIC ENDOMETRIAL CANCER - Young Je Choi; Min Jeong Kwon; Hyun Goo Kang; Kang Hyun Kim; Min Kim (RETINAL Cases & Brief Reports, 2026)
Purpose: To report a rare and fulminant case of Clostridium septicum endogenous endophthalmitis. Methods: A case report of a 52-year-old woman with metastatic endometrial cancer who developed sudden vision loss in the left eye 10 hours after presenting with dizziness, moderate fever, and a normal brain computed tomography scan. Results: The left eye had no light perception. Slit-lamp examination revealed corneal edema and mild anterior chamber inflammation. Owing to a limited fundus view, B-scan ultrasonography was performed, revealing a subretinal hypoechoic lesion with posterior shadowing. Orbital computed tomography subsequently demonstrated intraocular gas pockets, suggesting gas-forming endophthalmitis. Early vitrectomy was performed because of rapid clinical deterioration, but progressive ocular necrosis necessitated enucleation. Clostridium septicum was confirmed in both vitreous and blood cultures. A follow-up abdominal computed tomography revealed a colonic metastasis. Conclusion: Clostridium septicum endophthalmitis is a rare, fulminant intraocular infection associated with malignancies. The presence of intraocular gas formation on early imaging should raise suspicion for gas gangrene endophthalmitis, and prompt immediate intervention, though visual prognosis remains extremely poor.